1996
DOI: 10.1136/bmj.312.7037.999
|View full text |Cite|
|
Sign up to set email alerts
|

Inequality in income and mortality in the United States: analysis of mortality and potential pathways

Abstract: Variations between states in the inequality of the distribution of income are significantly associated with variations between states in a large number of health outcomes and social indicators and with mortality trends. These differences parallel relative investments in human and social capital. Economic policies that influence income and wealth inequality may have an important impact on the health of countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
592
1
25

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 998 publications
(646 citation statements)
references
References 13 publications
19
592
1
25
Order By: Relevance
“…Furthermore, as persons with high educational attainment are likely to have had access to public goods during their education, they may actively contribute to social welfare and cohesion, which would improve the general population health. Our results extend previous work in suggesting that the influence of education distribution and income distribution differ with respect to health and health behaviors (Kawachi and Kennedy, 1999;Kaplan et al, 1996;Galea and Ahern, 2005). Specifically, while maldistribution of income was associated with a higher number of drinks consumed among those who drink, maldistribution of education was associated with a lower number of drinks consumed among those who drink.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, as persons with high educational attainment are likely to have had access to public goods during their education, they may actively contribute to social welfare and cohesion, which would improve the general population health. Our results extend previous work in suggesting that the influence of education distribution and income distribution differ with respect to health and health behaviors (Kawachi and Kennedy, 1999;Kaplan et al, 1996;Galea and Ahern, 2005). Specifically, while maldistribution of income was associated with a higher number of drinks consumed among those who drink, maldistribution of education was associated with a lower number of drinks consumed among those who drink.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of height, it is possible that this lies on the causal pathway between inequality and health. Previous studies have found associations between inequality and low birth-weight (Kaplan et al 1996;Shi et al 2004), which suggests that pre-natal exposure to inequality may have a detrimental effect on physical development, and potentially therefore on attained height. It is also possible that development could be affected by post-natal stress caused by inequality (Mascie-Taylor 1991).…”
Section: Discussionmentioning
confidence: 95%
“…Al comparar las tasas de homicidios entre países -o entre áreas geográficas de un mismo país -diversos autores han hecho énfasis en la relación existente entre pobreza, desigualdad social y crimen violento, y en la necesidad de un análisis que tome en cuenta las diferencias espaciales para explicar las posibles variaciones de las tasas de homicidios en un territorio determinado (Kaplan et al, 1996;Kawachi, 2000;Kennedy et al, 1999;.…”
Section: Introductionunclassified